THE MELIPO TRADITION IN THE MANDAR COMMUNITY OF MAJENE REGENCY: AN ISLAMIC EDUCATIONAL REVIEW - Fathani, Hamzah S.; Usri, Usri; Saddang, Muhammad; Mohammadi, Ghasem (Balai Penelitian dan Pengembangan Agama Makassar, 2024)
This research aims to find out the form of implementation of melipo in the Mandar community and the perspective of Islamic education regarding the implementation of melipo in the Mandar community. This type of research is qualitative, with surveys, in-depth interviews, and documentation as data collection methods. The results of this study show that the implementation of melipo in the Mandar community is carried out at certain times, starting from the second day after the burial of the body until three or seven days later. Apart from that, melipo is carried out by several people, such as the priest (who will pray), family, and neighbors or friends, while carrying certain objects required for the melipo activity. The perspective of Islamic education regarding the implementation of melipo in Mandar society is in line with the Al-Qur'an, hadith, and the views of Muslim scholars or scholars. It can be seen from the educational values contained in the melipo tradition, such as that the world is not an eternal place; no one can escape death; graves are humans’ last place; Zuhud is the authenticity of life in the world; bringing up feelings of humanity, creating a sense of empathy, eroding arrogance, avoiding greed or covetousness; unity is very important; helping is urgently needed; brotherhood between people needs to be maintained; praying for those who preceded you; and reflection on attitudes and behavior.